Thermal-Energy Performance of Bulk Insulation Coupled with High-Albedo Roof Tiles in Urban Pitched Residential Roof Assemblies in the Hot, Humid Climate - Dahim, M. (MDPI, 2022)
The high rate of heat transfer through the residential roof assembly aggravates the condition of indoor thermal discomfort. Bulk insulation can be installed in the assembly to improve thermal performance. However, although it can efficiently reduce diurnal heat transfer from the outdoor environment into the indoor space through the roof assembly, it can also suppress nocturnal heat transfer in the opposite direction. Alternatively, high-albedo roof tiles employ cool colors to reflect heat at the roof surface, whereas bulk insulation hinders the conduction of heat through the roof assembly. In light of the potential of high-albedo roof tiles and bulk insulation in reducing heat transfer, thermal-energy performance of an urban pitched residential roof assembly, which adopted varying configurations of high-albedo roof tiles and bulk insulation under a hot, humid climate, was evaluated. Energy savings were generated, which were 15.13 when the change from a conventional to a high-albedo roof surface was performed, and 17.00 when the installation of bulk insulation was performed on the high-albedo roof assembly. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.